Relationship between personality traits, parental attachment, locus of control and acculturation with psychological well-being of Iranian adolescents in Malaysia - Mobarakeh, Mohammad Reza Vakili (2015)
Factors influencing adolescent psychological well-being have always been the basic issues in adolescent adjustments. Psychological well-being among the Iranian adolescents who migrate is one of the most important subjects in the foreign countries. Many studies have examined the important factors of adolescent psychological wellbeing. However, very limited research has focused on the basic role of personality traits, parental attachment, locus of control and acculturation on psychological wellbeing particularly among the Iranian adolescents who live in Kuala Lumpur, Malaysia. Therefore, the main aims of this study were to examine whether personality traits, parental attachment, and locus of control simultaneously predict adolescent psychological well-being. Furthermore, this study examined the role of acculturation as a mediator for the relationships between the personality traits, parental attachment, locus of control, and psychological well-being. Correlational research design were used, involving 300 male and female Iranian high school students with the age range of 13-16 years in Kuala Lumpur. The participants were identified by using cluster random sampling technique. The instruments used for data collection comprised Psychological Well-being Scale, (Ryff and Keyes, 1995), Five Factor Inventory (NEO-FFI) (Costa and McCrae, 1992), Inventory of Parent and Peer Attachment (IPPA) (Armsden and Greenberg, 1987), Locus of Control Scale, (Rotter, 1966) and Acculturation Scale, (Landrine and Klonooff, 1994). The results of the Pearson correlation analysis showed that age and family income of the participants were not significantly related to psychological well-being, however personality characteristics, parental attachment, and locus of control were significantly correlated with psychological well-being. The t-test result also indicated that there was not any significant difference between males and females in psychological well-being. In addition, the Hierarchical Regression analyses indicated that personality traits, parental attachment, and locus of control were significant contributors to psychological well-being with acculturation as the strongest predictor in adolescent psychological well-being.